Oxidative desulfurization of dibenzothiophene catalyzed by α-MnO2 nanosheets on palygorskite using hydrogen peroxide as oxidant. Issue 32 (16th May 2018) - Yu, Xingming; Han, Pingfang; Li, Ya
Abstract : Palygorskite (Pal)-supported α-MnO2 nanosheets (Ns-MnPal) combine the adsorption features of Pal with the catalytic properties of α-MnO2 nanosheets. Abstract : Palygorskite (Pal)-supported α-MnO2 nanosheets (Ns-MnPal) combine the adsorption features of Pal with the catalytic properties of α-MnO2 nanosheets. They were prepared and examined in the catalytic oxidative desulfurization (ODS) of dibenzothiophene (DBT) from a model oil employing 30 wt% H2 O2 as the oxidant under mild conditions. The supported catalyst was fabricated by the solvothermal method, and effective immobilization of α-MnO2 nanosheets was confirmed by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), thermogravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS) and N2 adsorption. The influence of various solvents, solvent volume, reaction temperature, reaction time, catalyst amount and H2 O2 /sulfur molar ratio on ODS was investigated. Using 20 mL of acetonitrile as a solvent, maximum sulfur removal of 97.7% was achieved for ODS of DBT in 1.5 h using a Ns-MnPal/oil ratio of 0.2 g L −1, reaction temperature of 50 °C and H2 O2 /sulfur molar ratio of 4. As solid catalysts, supported α-MnO2 nanosheets could be separated from the reaction readily. The catalyst was recycled seven times and showed no significant loss in activity.